On Philosophical Prerequisites of Lenin’s Idea of Reflection as the Universal Quality of the Matter - Jakušovaitė, Irena (Problemos, 1980)
The starting point in the present paper is the assumption that Lenin’s idea comprises two interrelated propositions: the matter possesses a quality comparable with sensation: this quality is the capacity for reflection. These two ideas were considered by philosophers of different epochs and schools. The author of the present paper draws a conclusion that Lenin’s idea of reflection as the universal quality of the matter is a dialectical synthesis derived from philosophical knowled.ge and concrete scientific data.